Prêter son nom et simuler des transactions. Des stipulations d’Abû Ja‘far al-Ṭaḥâwî (ixe-xe siècles) aux consultations et actes juridiques des xviie-xviiie siècles - Brigitte Marino (Revue des Mondes Musulmans et de la Méditerranée)
A careful study of the recorded legal acts of eighteenth century Damascus courts suggests that parties to real property transactions - both buyers and sellers – acted sometimes for undisclosed third parties without being explicitly qualified as their proxy. Contrary to appearances, then, the real protagonists of these transactions were not necessarily those named in the documents.Collections of legal opinions (fatâwâ) and works of legal subterfuge (ḥiyal) refer to two phenomena related to this kind of situation: the use of straw men and the simulation of transactions. Most illuminating here is a handbook of legal stipulations (shurûṭ) written by a medieval Egyptian jurist, Abû Ja‘far al-Ṭaḥâwî, that allows us to seriously reconsider our approach to court records.After a brief discussion of the formularies concerning the use of a straw man and the simulation of transactions as proposed by Ṭaḥâwî, this article considers some of the fatâwâ of the Ottoman period dealing with these issues and examines how such transactions appear in legal acts and court records of Ottoman Damascus.